Molecular-Level Studies on Dynamic Behavior of Oligomeric Chain Molecules in Porous Coordination Polymers - Uemura, Takashi; Washino, Gosuke; Kitagawa, Susumu; Takahashi, Hirohide; Yoshida, Aiko; Takeyasu, Kunio; Takayanagi, Masayoshi; Nagaoka, Masataka (Journal of physical chemistry. C, 2015)
The quest for porous coordination polymers (PCPs) has been the subject of intense research because of their unique porous functions. Although considerable attention has been paid to the behavior of gases and low-molecular-weight compounds in PCPs, the study of adsorption, diffusion, and interaction of macromolecules, including oligomers and polymers, in PCPs at the molecular level has been limited to date. Here, we have studied the dynamic behavior of oligomeric chain molecules, both theoretically and experimentally, in [Zn2(bdc)2(ted)] n (1; bdc = 1,4-benzenedicarboxylate, ted = triethylenediamine). Molecular dynamics simulations revealed that the motion of linear oligomeric chains, such as oligo(ethylene glycols) or paraffins, is composed of smooth transfer along the large channels and slow transfer to the adjacent channels by penetrating the narrow apertures of 1. Moreover, this anisotropic behavior depends on the polarity of the guest chains because of the Coulomb interactions with the polarized aperture surface. Atomic force spectroscopy was also performed, for the first time, in an effort to probe directly the host–guest unbinding forces occurring at the molecular level in PCPs. Specific interactions of oligomers immobilized on an atomic force microscope cantilever with the PCP nanopores could be detected. This was likely caused by desorption of the guest molecules from the PCP pores, which agrees with the molecular behavior shown by the theoretical study. A quantitative understanding of macromolecular behavior in PCPs at the molecular level will provide important guidelines for the development of functional host–guest nanocomposites.